2021
DOI: 10.1093/eurheartj/ehab421
|View full text |Cite
|
Sign up to set email alerts
|

Predictors, time course, and outcomes of persistence patterns in oral anticoagulation for non-valvular atrial fibrillation: a Dutch Nationwide Cohort Study

Abstract: Aims  Persistence with direct oral anticoagulants (DOACs) has become a concern in non-valvular atrial fibrillation (NVAF) patients, but whether this affects prognosis is rarely studied. We investigated the persistence with oral anticoagulants (OACs) and its association with prognosis among a nationwide cohort of NVAF patients. Methods and results  DOAC-naive NVAF patients who started to use DOACs for ischaemic stroke preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 50 publications
6
58
2
Order By: Relevance
“…Adherence and persistence with OAC is vital for achieving a clinical benefit of stroke prophylaxis. 10,25,26 Monitoring warfarin therapy allows for some treatment control related to continuous dose adjustments, but suboptimal adherence has been reported in one third of all AF Note: Data present the % (number of patients) or the median (interquartile range), as indicated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adherence and persistence with OAC is vital for achieving a clinical benefit of stroke prophylaxis. 10,25,26 Monitoring warfarin therapy allows for some treatment control related to continuous dose adjustments, but suboptimal adherence has been reported in one third of all AF Note: Data present the % (number of patients) or the median (interquartile range), as indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring warfarin therapy allows for some treatment control related to continuous dose adjustments, but suboptimal adherence has been reported in one third of all AF patients 27,28 . Although DOAC treatment does not require routine monitoring, some studies dispute that patients treated with DOAC should be prone to non‐adherence in daily clinical practice, 16,29 whereas others have found that one in four patients did not persist with recommended DOAC therapy over four years, 10,22 None of these studies focused on OAC treatment patterns in patients with incident cancer, and comparison of persistence across studies are challenged by methodological differences. Our estimated one‐year incidence of DOAC discontinuation of 26% is lower than reported in a previous meta‐analysis showing persistence at 62%; however, this was not focused on patients with cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of monitoring, however, may contribute to suboptimal treatment persistence to DOACs, which was identified by several observational studies. [11][12][13][14] Although NVAF patients who receive VKAs but with a low TTR are suggested to switch to a DOAC, 2 it is unknown whether the switch improves the persistence to oral anticoagulation. This question is relevant because non-persistence to OAC was associated with an increased risk of ischemic stroke in DOAC users.…”
Section: Introductionmentioning
confidence: 99%